(untitled) (Brazilian Geographical Journal, 2012)
A BRIEF DISCUSSION OF GENERAL ASPECTS OF BIODIESEL PRODUCTION. Environmental concerns dominate the world scene in the XXI century. The petroleum and its derivatives are a major contributor to the non-renewable sources of energy. However, there are forecasts that in a time near the main sources of petroleum may exhaust. Thus, the search for alternative sources of energy, beside environmental necessity is essential to ensure the well being of all. The mineral diesel, the main petroleum derivative, is an extremely fuel used. Its use in diesel engines leads to high rates of emission of greenhouse gases. A potential substitute for diesel fuel is biodiesel. Biodiesel consists of alkyl esters of long chain carboxylic acids, from renewable sources such as vegetable oils or animal fats. The introduction of biodiesel in the energy matrix has been stimulated by environmental factors, where studies have shown that the burning of biodiesel leads to significant reduction of greenhouse gases, and also economic and social factors.